The inner ear : including otoneurology, otosurgery, and problems in modern warfare - Fischer, Joseph; Wolfson, Louis E. (William Heinemann, 1943)
The Inner Ear: Including Otoneurology, Otosurgery, and Problems in Modern Warfare covers the anatomical, physiological and the central pathways of the inner ear. This book is composed of 15 chapters that particularly consider the pathologic anatomy of the various forms of labyrinthine diseases. The first three chapters deal with the clinical anatomy and physiological features of the inner ear. The next chapter examines certain conditions that can be observed during induced and abnormal excitability of the labyrinth. These topics are followed by considerable chapters on various forms of labyrin.